PRAGMATICS ANALYSIS ON REFUSAL AND POLITENESS STRATEGIES IN HOME ALONE MOVIE BY JOHN HUGHES - Hendar .; Meiga Maudina Siti Anshari (Universitas Widyatama, 2021)
This research aims at identifying the types of refusal strategy and the types of politeness strategy found in the refusal acts in Home Alone movie directed by John Hughes and to get the data needed in this research, the writer did the following steps: choosing and watching the movies, transcribing the dialogue, selecting the data, classifying and giving codes to the obtained data, analyzing the data and drawing a conclusion related to the types of refusal strategy and the politeness strategy. The theoretical framework used in this research is related to the types of refusal strategies by Beebe, et al. and for the politeness strategy the writer used the theory from Brown and Levinson (1987). The results of this research show that of 35 obtained data on (1) the types of refusal strategy, there are 13 data (37.14%) of non-performative verbs of direct refusal strategy and 22 data (62.86%) of indirect refusal strategies consisting of 8 data (22.86%) of avoidance, 8 data (22.86%) of excuse/ reason/ explanation, 3 data (8.57%) of promise of future acceptance, 1 data (2.86%) of set condition for future or past acceptance, 1 data (2.86%) of statement of principle/ philosophy, dan 1 data (2.86%) of acceptance that functions as a refusal and; (2)on the types of politeness, there are 17 data (48.57%) of bald on record strategy, 9 data (25.71%) of positive politeness strategy, 5 data (14.29%) of negative politeness strategy, and 4 data (11.43%) of off record strategy.